Karakteristik Faktor Penentu Keputusan Belanja Online - Yanto, Deri; Siregar, Nurhayati; Suryana, Melda (EKONOMI DAN BISNIS DIGITAL, 2024)
The pandemic that has lasted since 2020 until now has made most people decide to shop online. Many factors be the reasons why someone makes a decision to shop online. This study aims to describe the characteristics of the driving and inhibiting factors for online shopping decisions during the 2022 pandemic. The research method is descriptive with a cross-sectional study using an online survey google form with voluntary online responsive survey and obtained 251 respondents. The results showed that the reasons for driving online shopping decisions were 80.1% practical, cost and time efficient, 60.2% cheaper price factor, 55.8% ease of comparing and choosing products, 50.6% free shipping facilities, 40,6% discount / sale, 39.8% promotional factors, Reasons of hesitation to shop online are 61.8% the quality of the goods is not as expected, 57.8% the product does not match the description, 35.9% doubts the authenticity of the goods, 33 ,5% worried about being lied to by the seller. The price factor, security during the pandemic, convenience, easyness are the reasons for driving motivational online shopping during the pandemic,